Mechanistic Insights into a Chiral Phosphoric Acid-Catalyzed Asymmetric Pinacol Rearrangement - Falcone, Bruno Nicolas (2018)
The first catalytic enantioselective pinacol rearrangement was reported by Antilla and co-workers in 2010. The reaction was catalyzed by a chiral phosphoric acid and resulted in high levels of enantioselectivity (up to 96% ee). The present study uses density functional theory to investigate the mechanism and origins of stereoselectivity of this important reaction and to explain the difference in selectivity between different catalysts. An OH···O hydrogen bond between the intermediate indolyl alcohol and the phosphate group from the catalyst together with a CH···O hydrogen bond between the indole and the phosphate group were observed in the preferred activation mode for the stereodetermining [1,2]-aryl shift. A stronger CH···O interaction in the major transition state was found to contribute to the high levels of enantioselectivity. A more bulky catalyst (TRIP) was found to impede the formation of the key CH···O interaction, leading to lower levels of enantioselectivity.